A Contribution to the Environmental History of Aristocracy on the Example of Zofia Chomętowska - Praczyk, Małgorzata (Porównania, 2021)
The aim of this article is to present the issues of human-animal relationships that took place in the circles of the Polish aristocracy of the interwar period, based on the example of Zofia Chomętowska’s relationship with animals present in her life. This example shows the complexity and multi-level structure of the relationships that resulted from her social status, the fact of being a woman, and her individual tendency to build a close bond with selected species of animals. In the social network of relationships in which she was immersed, they served both as a hunting object, as food, as a sign of social status, and as friends. The analysis of the texts and photographs by the aristocrat shows a strong gender component and the fact that animals constituted a very important element in constructing the aristocratic social class. The environmental history of the Polish aristocracy in the interwar period in this part, that is represented by Chomętowska, is therefore both class-related and unique, due to the intimate and empathetic approach of the photographer to selected, anthropomorphized non-human subjects.